IL-15 Fosters Age-Driven Regulatory T Cell Accrual in the Face of Declining IL-2 Levels - Raynor, Jana; Sholl, Allyson; Plas, David R.; Bouillet, Philippe; Chougnet, Claire A.; Hildeman, David A. (Frontiers in Immunology, 2013)
We and others have shown that regulatory T cells (Treg) accumulate dramatically with age in both humans and mice. Such Treg accrual contributes to age-related immunosenescence as they reduce the response to tumors and parasite infection. While we reported earlier that aged Treg have decreased expression of the pro-apoptotic molecule Bim and germline deletion of Bim promoted earlier accumulation of Treg, it remains unclear whether the effects of Bim are (i) Treg intrinsic and (ii) dominant to other BH3 only pro-apoptotic molecules. Further, the mechanism(s) controlling Bim expression in aged Treg remain unclear. Here we show that Treg-specific loss of Bim is sufficient to drive Treg accrual with age and that additional loss of the downstream apoptotic effectors Bax and Bak did not exacerbate Treg accumulation. Further, our results demonstrate that a subpopulation of Treg expands with age and is characterized by lower expression of CD25 (IL-2R) and Bim. Mechanistically, we found that IL-2 levels decline with age and likely explain the emergence of CD25loBimlo Treg because Treg in IL-2-/- mice are almost entirely comprised of CD25loBimlo cells, and IL-2 neutralization increases CD25loBimlo Treg in both young and middle-aged mice. Interestingly, the Treg population in aged mice had increased expression of CD122 (IL-2/IL-15R) and neutralization or genetic loss of IL-15 led to less Treg accrual with age. Further, the decreased Treg accrual in middle-aged IL-15-/- mice was restored by the additional loss of Bim (IL-15-/-Bim-/-). Together, our data show that aging favors the accrual of CD25lo Treg whose homeostasis is supported by IL-15 as IL-2 levels become limiting. These data have implications for manipulating Treg to improve immune responses in the elderly.